m3g=m1g+m2g
Akash Anand Not the right approach
Ayush Lodha if we know the which mass is greater m1 or m2 ,sir we can then get the condition by constraint relation
If T is the tension in the string joining m3 and T' be the tension in the string joining m1 to m2.
Without loss of generality we can assume m1>m2.
a be the acc of m3 upwards and a' be the acc. of m1 downwards.
Then,
m1g - T' = m1a + m1a'.....(1)
T' - m2g= m2a' - m2a....(2)
T - m3g = m3a.....(3)
Substituting T = 2T' and a=0 we get the required result.
m3g=m1g+m2g
Tension in the string should be. m2g(1+m1-m2) by (m1+m2)
i.e m3g= to the expression above
and the acc. In the blocks m1 and m2 should be---
(g(m1-m2))/(m1+m2)
m1=m2=m32......??
(if u consider pulley to be massless...)
@Dwijaraj...can u pls explain how u got it...i mean the equations??
T=[|m1-m2|+(m1+m2)]*m2g/(m1+m2)
also T=[|m1-m2|-(m1+m2)]*m1g/(m1+m2)
so m3=2*[|m1-m2|+(m1+m2)]/(m1+m2)
or we can also say m3=T+T
=[|m1-m2|+(m1+m2)]*m2g/(m1+m2)+
[|m1-m2|-(m1+m2)]*m1g/(m1+m2)
SO m3=|m1-m2|-(m2-m1)
now if m1>m2
m3=2(m1-m2)
if m1<m2
m3=0,which is not possible
so m3=2(m1-m2)
Till now ..No one is even close to the right answer. Keep trying.
if T is the tension in string connecting m1 and m2 then
2T=m3g
also T-m1g=m1a....(i)
m2g-T=m2a....(ii)
solving (i) and (ii) we get
|a|=|m1-m2|*g/(m1+m2)
so putting this in eq(i) we get
T=m1(m2-m1)*g/(m1+m2) + m1g(as we have assumed a for m1 in upward direction)
T=m1m2g/(m1+m2)
so m3=2T=2m1m2/(m1+m2)
if T is the tension in string connecting m1 and m2 then
2T=m3g
also T-m1g=m1a....(i)
m2g-T=m2a....(ii)
solving (i) and (ii) we get
|a|=|m1-m2|*g/(m1+m2)
so putting this in eq(i) we get
T=m1(m2-m1)*g/(m1+m2) + m1g(as we have assumed a for m1 in upward direction)
T=m1m2g/(m1+m2)
so m3=2T=2m1m2/(m1+m2)
m3= (m1-m2)/(m1+m2)+ m2...considering. m1 is more than m2
m3 = 4m1m2/m1+m2